The school newspaper: a resource for teacher research (Journal of Parents and Teachers, 2014)
In order to improve the quality of education, it is necessary that teachers begin to carry out a delicate task of reflection on their own teaching activity. To do this, a tool that can be used is the teacher's class diary, a personal document written by the teacher in which his impressions of what happens in class are collected.
Keywords: teacher reflection; educational quality; teacher's diary.